Antecedents of Customer Citizenship Behavior in Local Coffee Shops - Jofira, Hilda; Sabur, Moch.; Fadhilah, Dylan Achmad (Fakultas Ekonomi Universitas Kadiri, 2025)
This research aims to analyze the influence of price justice, procedural justice, customer trust, customer satisfaction, and customer loyalty on customer citizenship behavior. The sampling technique in this research used